Imagens em contraponto: um estudo de semiologia icônica aplicado a fotografias de imprensa - Chamarelli Filho, Milton (Cadernos de Linguagem e Sociedade, 2010)
The present work is an investigation of photos published in a widely read magazine in Brazil, in a period previous to the presidential elections of 1994. Based on semiological analysis, we attempted to observe strategies which can add to the candidates’ profile through their wives’ images.